Genetic Factors in Nonsyndromic Orofacial Clefts - Khan, Mahamad Irfanulla; CS, Prashanth; Srinath, Narasimha Murthy (Global Medical Genetics, 2020)
Orofacial clefts (OFCs) are the most common congenital birth defects in humans and immediately recognized at birth. The etiology remains complex and poorly understood and seems to result from multiple genetic and environmental factors along with gene–environment interactions. It can be classified into syndromic (30%) and nonsyndromic (70%) clefts. Nonsyndromic OFCs include clefts without any additional physical or cognitive deficits. Recently, various genetic approaches, such as genome-wide association studies (GWAS), candidate gene association studies, and linkage analysis, have identified multiple genes involved in the etiology of OFCs.This article provides an insight into the multiple genes involved in the etiology of OFCs. Identification of specific genetic causes of clefts helps in a better understanding of the molecular pathogenesis of OFC. In the near future, it helps to provide a more accurate diagnosis, genetic counseling, personalized medicine for better clinical care, and prevention of OFCs.
Keywords: orofacial clefts; nonsyndromic; genetics; gene mutation; genome-wide association study; linkage analysis